Cross-linguistic Semantics of International Law. A corpus-informed translation of A. Cassese’s International Law into Greek - Saridakis, Ioannis E (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This paper elaborates and exemplifies systemic hypotheses on the emergence and evolution of international legal language semantics, focusing in particular on the analysis of international law concepts and the study of their representation and translation into Greek. Non-exhaustive examples are taken from the translation of A. Cassese's International Law into Greek, an effort aimed to illustrate the process of translation in the domain of international law, as being primarily a venture of discoursal decoding.